Growth of Gram-Negative Bacteria in Antiseptics, Disinfectants and Hand Hygiene Products in Two Tertiary Care Hospitals in West Africa-A Cross-Sectional Survey - AFFOLABI, DISSOU (My University, 2023)
Antiseptics, disinfectants, and hand hygiene products can act as reservoirs of Gram-negative bacteria causing healthcare-associated infections. This problem is rarely documented in low- and middle-income countries, particularly in sub-Saharan Africa. In a cross-sectional survey, we assessed the bacterial contamination of antiseptics, disinfectants, and hand hygiene products in two university hospitals in Burkina Faso and Benin. During ward visits and staff interviews, in-use products were cultured for the presence of Gram-negative bacteria. The growth of Gram-negative bacteria was absent or rare in alcohol-based products, povidone iodine, and Dakin solution. Contamination was highest (73.9% (51/69)) for liquid soap products (versus antiseptic/disinfectants (4.5%, 7/157) (p < 0.0001)), mostly used in high-risk areas and associated with high total bacterial counts (>10,000 colony-forming units/mL). Contaminating flora (105 isolates) included Enterobacterales and the Vibrio non-cholerae/Aeromonas group (17.1%) and non-fermentative Gram-negative rods (82.8%). Multidrug resistance was present among 9/16 Enterobacterales (Klebsiella and Enterobacter spp.) and 3/12 Acinetobacter spp., including carbapenem resistance (Acinetobacter baumannii: NDM, Pseudomonas stutzeri: VIM). The risk factors for contamination included the type of product (cleaning grade and in-house prepared liquid soap), use of recycled disposable containers and soft drink bottles, absence of labeling, topping-up of containers, dilution with tap water (pharmacy and ward), and poor-quality management (procurement, stock management, expiry dates, and period after opening). Keywords: Gram-negative; West Africa; antiseptics; bacteria; cross-sectional; disinfectants; hand hygiene; healthcare-associated infections; low-and middle-income countries; resistance.
Keywords: Keywords: Gram-negative; West Africa; antiseptics; bacteria; cross-sectional; disinfectants; hand hygiene; healthcare-associated infections; low-and middle-income countries; resistance.